Molecular Diversity of Trypanosoma cruzi Detected in the Vector Triatoma protracta from California, USA. - Lisa A Shender; Michael D Lewis; Daniel Rejmanek; Jonna A K Mazet (Public Library of Science (PLoS), 2016)
BACKGROUND:Trypanosoma cruzi, causative agent of Chagas disease in humans and dogs, is a vector-borne zoonotic protozoan parasite that can cause fatal cardiac disease. While recognized as the most economically important parasitic infection in Latin America, the incidence of Chagas disease in the United States of America (US) may be underreported and even increasing. The extensive genetic diversity of T. cruzi in Latin America is well-documented and likely influences disease progression, severity and treatment efficacy; however, little is known regarding T. cruzi strains endemic to the US. It is therefore important to expand our knowledge on US T. cruzi strains, to improve upon the recognition of and response to locally acquired infections. METHODOLOGY/PRINCIPLE FINDINGS:We conducted a study of T. cruzi molecular diversity in California, augmenting sparse genetic data from southern California and for the first time investigating genetic sequences from northern California. The vector Triatoma protracta was collected from southern (Escondido and Los Angeles) and northern (Vallecito) California regions. Samples were initially screened via sensitive nuclear repetitive DNA and kinetoplast minicircle DNA PCR assays, yielding an overall prevalence of approximately 28% and 55% for southern and northern California regions, respectively. Positive samples were further processed to identify discrete typing units (DTUs), revealing both TcI and TcIV lineages in southern California, but only TcI in northern California. Phylogenetic analyses (targeting COII-ND1, TR and RB19 genes) were performed on a subset of positive samples to compare Californian T. cruzi samples to strains from other US regions and Latin America. Results indicated that within the TcI DTU, California sequences were similar to those from the southeastern US, as well as to several isolates from Latin America responsible for causing Chagas disease in humans. CONCLUSIONS/SIGNIFICANCE:Triatoma protracta populations in California are frequently infected with T. cruzi. Our data extend the northern limits of the range of TcI and identify a novel genetic exchange event between TcI and TcIV. High similarity between sequences from California and specific Latin American strains indicates US strains may be equally capable of causing human disease. Additional genetic characterization of Californian and other US T. cruzi strains is recommended.